Anterolateral Knee Extra-articular Stabilizers: A Robotic Sectioning Study of the Anterolateral Ligament and Distal Iliotibial Band Kaplan Fibers. Issue 6 (May 2018) - Geeslin, Andrew G.; Chahla, Jorge; Moatshe, Gilbert; Muckenhirn, Kyle J.; Kruckeberg, Bradley M.; Brady, Alex W.; Coggins, Ashley; Dornan, Grant J.; Getgood, Alan M.; Godin, Jonathan A.; LaPrade, Robert F.
Background: The individual kinematic roles of the anterolateral ligament (ALL) and the distal iliotibial band Kaplan fibers in the setting of anterior cruciate ligament (ACL) deficiency require further clarification. This will improve understanding of their potential contribution to residual anterolateral rotational laxity after ACL reconstruction and may influence selection of an anterolateral extra-articular reconstruction technique, which is currently a matter of debate. Hypothesis/Purpose: To compare the role of the ALL and the Kaplan fibers in stabilizing the knee against tibial internal rotation, anterior tibial translation, and the pivot shift in ACL-deficient knees. We hypothesized that the Kaplan fibers would provide greater tibial internal rotation restraint than the ALL in ACL-deficient knees and that both structures would provide restraint against internal rotation during a simulated pivot-shift test. Study Design: Controlled laboratory study. Methods: Ten paired fresh-frozen cadaveric knees (n = 20) were used to investigate the effect of sectioning the ALL and the Kaplan fibers in ACL-deficient knees with a 6 degrees of freedom robotic testing system. After ACL sectioning, sectioning was randomly performed for the ALL and the Kaplan fibers. An established robotic testing protocol was utilized to assess knee kinematics when the specimens were subjected to a 5-N·m internal rotation torque (0°-90° at 15° increments), a simulated pivot shift with 10-N·m valgus and 5-N·m internal rotation torque (15° and 30°), and an 88-N anterior tibial load (30° and 90°). Results: Sectioning of the ACL led to significantly increased tibial internal rotation (from 0° to 90°) and anterior tibial translation (30° and 90°) as compared with the intact state. Significantly increased internal rotation occurred with further sectioning of the ALL (15°-90°) and Kaplan fibers (15°, 60°-90°). At higher flexion angles (60°-90°), sectioning the Kaplan fibers led to significantly greater internal rotation when compared with ALL sectioning. On simulated pivot-shift testing, ALL sectioning led to significantly increased internal rotation and anterior translation at 15° and 30°; sectioning of the Kaplan fibers led to significantly increased tibial internal rotation at 15° and 30° and anterior translation at 15°. No significant difference was found when anterior tibial translation was compared between the ACL/ALL- and ACL/Kaplan fiber–deficient states on simulated pivot-shift testing or isolated anterior tibial load. Conclusion: The ALL and Kaplan fibers restrain internal rotation in the ACL-deficient knee. Sectioning the Kaplan fibers led to greater tibial internal rotation at higher flexion angles (60°-90°) as compared with ALL sectioning. Additionally, the ALL and Kaplan fibers contribute to restraint of the pivot shift and anterior tibial translation in the ACL-deficient knee. Clinical Relevance: This study reports that the ALL and distal iliotibial band Kaplan fibers restrain anterior tibial translation, internal rotation, and pivot shift in the ACL-deficient knee. Furthermore, sectioning the Kaplan fibers led to significantly greater tibial internal rotation when compared with ALL sectioning at high flexion angles. These results demonstrate increased rotational knee laxity with combined ACL and anterolateral extra-articular knee injuries and may allow surgeons to optimize the care of patients with this injury pattern.